Resentralisasi Dalam Pembagian Kewenangan Pemanfaatan Energi Panas Bumi - Prabowo, Canggih (Faculty of Law, Parahyangan Catholic University, 2016)
AbstractThe promulgation of Law no. 23 of 2014 re. Local Government, strengthening local government’s authority, is expected to provide a way out to the problem of how to harvest geothermal energy found in forest protected areas (within the jurisdiction of local government) to supply the increasing demand for electricity throughout Indonesia. For more than 10 years after the promulgation of Law no. 32 of 2004, the central government program to accelerate the utilization of geothermal energy source found within protected forest zones had come to a full stop. This article discusses the issue of how government authority (central-local) related to the above problem had been distributed and the existing tension between central-local government. The central government tendency to take back authorities previously granted to local authorities defies the whole effort at making government more accountable, efficient and prevention of externalities.